A Case of Hageman-Factor Deficiency and a Method to Purify the Factor - Haanen, C; Hommes, F; Benraad, H; Morselt, G (Thrombosis and Haemostasis, 1961)
1. Description of a new case of Hageman factor deficiency. The patient’s plasma was used for a quantitative estimation of the Hageman factor in normal plasma.2. By means of adsorption on to glass and elution at pH 9.6 followed by salting out procedures, it was possible to obtain a concentrated HF preparation, free from any other known coagulation factors.3. There were strong indications for the assumption that the activation of HF does not take place by releasing any inhibitor. It could result from a dissociation by the glass surface of a less active protein into two or more active factors.4. The slight inhibition which HF deficient plasma exerts on the activation of normal plasma is possibly caused by the occupation of the glass surface by non-specific proteins from HF deficient plasma.5. In plasma HF is reversibly bound to other non-specific proteins in the ß and y globulin fraction.6. After the activation by a glass surface the HF is still active in siliconed glass-ware.